If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -39 = -3y Solving -39 = -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -39 + 3y = -3y + 3y Combine like terms: -3y + 3y = 0 -39 + 3y = 0 Add '39' to each side of the equation. -39 + 39 + 3y = 0 + 39 Combine like terms: -39 + 39 = 0 0 + 3y = 0 + 39 3y = 0 + 39 Combine like terms: 0 + 39 = 39 3y = 39 Divide each side by '3'. y = 13 Simplifying y = 13
| -15=-5/9x | | y^2-28y+64=0 | | -3z/5=9 | | 2(v+5)-8v=28 | | -3/2c=-3 | | -3/2c=-13 | | -3/3c=-13 | | 1xX=15 | | (21b-6)-5(4b+1)=-2 | | 5x-8=4(x-6) | | 25x^6/6 | | -6(7-3m+n)=-42+18m-6n | | 6x+12=92 | | x^3+y^3-3xy+1=0 | | x-5/2-4=x-7/3 | | Logx^1/49=-2 | | 9x-(6x+3)=5x-11 | | 6=(120x)/(x^2-200) | | 0.16x+x=7 | | 6x+5y=2forx | | 9x+2=4x-3 | | x=10+1.5y | | -4(2x-3)=2(x+4) | | 12v^2+29v+15= | | 2(x-1)=9x-37 | | 3(2x-8)=5(2x+8) | | -14-2k=-8-5(-8+5k) | | 16=8+(-a) | | 0.15y+0.08(y+4000)=1240 | | f(x)=2.45x^2-6.13x-3.68 | | 6-5(2x+3)=11 | | 2(x+4)+7x=3(x+4) |